2001
DOI: 10.1051/anphys:200101001
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic equation for strongly interacting dense Fermi systems

Abstract: We review the non-relativistic Green's-function approach to the kinetic equations for Fermi liquids far from equilibrium. The emphasis is on the consistent treatment of the off-shell motion between collisions and on the non-instant and non-local picture of binary collisions. The resulting kinetic equation is of the Boltzmann type, and it represents an interpolation between the theory of transport in metals and the theory of moderately dense gases. The free motion of particles is renormalised by various mean fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(94 citation statements)
references
References 21 publications
1
93
0
Order By: Relevance
“…A correction of this asymmetry can be based on the concept of non-local and non-instant collisions [3]. However, this asymmetry may also be corrected by supplementing the Boltzmann description with a proper description of spatial variations of the molecules.…”
Section: Equilibrium Distribution and The Boltzmann Kinetic Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…A correction of this asymmetry can be based on the concept of non-local and non-instant collisions [3]. However, this asymmetry may also be corrected by supplementing the Boltzmann description with a proper description of spatial variations of the molecules.…”
Section: Equilibrium Distribution and The Boltzmann Kinetic Equationmentioning
confidence: 99%
“…The Boltzmann kinetic equation has received a number of derivations under specific assumptions which all aim to prove its physical and mathematical rigour [2]. It is also widely accepted that continuum fluid mechanical models, and associated classical thermodynamic models, in particular equations of state, can be obtained from the statistical kinetic formulations [3]. For example, it is well-known that the three classical fluid dynamic equations, the Navier-Stokes equations, may be derived from the Boltzmann kinetic equation [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, if they are not applied then a gradient expansion would become too cumbersome to be of use in practical calculations. The derivation of transport equations has been discussed in great detail in the literature [14,15,16,17,18,19,20,21,22,23,24,25,26]. Most discussions focus on kinetic theory employing the additional approximation of a suitable quasi-particle ansatz, which goes beyond assumptions 1) -3).…”
Section: Assumptionsmentioning
confidence: 99%
“…Although their discussion is limited to the equilibrium, it marks a way how to introduce virial corrections also to dynamical processes. The kinetic equation for quasiparticles with non-instantaneous and non-local scattering integral has been derived in [37,54] as a systematic quasi-classical limit of non-equilibrium Green's functions in the Galitskii-Feynman approximation. It has been shown that the gradient corrections to the scattering integral can be rearranged into a form of a collision delay and space displacements reminiscent of classical hard spheres, i.e., into a form suitable for numerical simulations.…”
Section: Theoretical Preliminariesmentioning
confidence: 99%
“…In this contribution we will put these ideas of nonlocalities on the firm ground using the quantum kinetic equation with nonlocal scattering integrals which was derived from quantum statistics [37,54] to show how the effect of nonlocalities play a role in simulations of heavy ion reactions and compare them with experiment.…”
Section: Theoretical Preliminariesmentioning
confidence: 99%